2013
DOI: 10.1371/journal.pone.0056030
|View full text |Cite
|
Sign up to set email alerts
|

Long Distance Bicycle Riding Causes Prostate-Specific Antigen to Increase in Men Aged 50 Years and Over

Abstract: ObjectivesTo investigate whether bicycle riding alters total prostate-specific antigen (tPSA) serum concentrations in healthy older men.Methods129 male participants, ranging in age from 50 to 71 years (mean 55 years), rode in a recreational group bicycle ride of between 55 and 160 kilometers. Blood samples for tPSA analysis were drawn within 60 minutes before starting, and within 5 minutes after completing the ride. The pre-cycling and post-cycling tPSA values were log transformed for normality and compared us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 34 publications
3
18
0
Order By: Relevance
“…By testing participants of the same age (about ≥50 years old), we mention two essential studies based on measurements of PSA in men after bicycle riding. Although the level of physical activity differed modestly, both studies describe an elevation in post-ride specimens [ 3 , 6 ] and, thus, are consistent with our findings. It is noteworthy that Kindermann et al showed that one hour cycle ergometer activity increased not only tPSA, but also fPSA [ 5 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…By testing participants of the same age (about ≥50 years old), we mention two essential studies based on measurements of PSA in men after bicycle riding. Although the level of physical activity differed modestly, both studies describe an elevation in post-ride specimens [ 3 , 6 ] and, thus, are consistent with our findings. It is noteworthy that Kindermann et al showed that one hour cycle ergometer activity increased not only tPSA, but also fPSA [ 5 ].…”
Section: Discussionsupporting
confidence: 91%
“…Long-distance biking is an excellent model to study the combined effects of mechanical prostate stimulation by bicycle riding and strenuous endurance exercise [ 2 ]. Mejak and coworkers demonstrated that cycling causes a significant increase in total PSA level when measured within 5 min post-cycling [ 3 ], whereas similar results were also achieved in other studies [ 4 , 5 , 6 , 7 ]. On the other hand, other researchers report no changes in PSA level following cycling [ 8 , 9 , 10 ], showing the controversy of these types of studies.…”
Section: Introductionsupporting
confidence: 74%
“…11,12 In addition to this, compression of the prostate gland and changes in venous flow dynamics have been suggested to increase PSA release, which helps to explain elevated PSA levels observed in some studies of cyclists. 13,14 As already discussed, increasing cycling levels in the population has huge potential gains for public health, particularly when only 4% of women and 6% of men reach current minimum guidelines regarding physical activity. 15 However, there is a need to understand fully the possible benefits and risks posed to current and prospective cyclists.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a study done in North Western Nigeria a higher prevalence of PSA results > 4 ng/ml was observed among farmers (11.77%) compared to business men (6.67%) and civil servants (5.66%) [9]. Physical activity such as cycling has also been shown to cause an increase in PSA levels among healthy males [15]. This is at variance with another study that linked less physical activity to elevated PSA levels [16].…”
Section: Discussionmentioning
confidence: 92%